Eksplorasi, Karakterisasi, dan Evaluasi Idiotipe Alpukat di Kabupaten Solok - Kuswandi Kuswandi; Liza Octriana; Bambang Kuswara; Nofiarli Nofiarli (JURNAL AGROTEKNOLOGI UNIVERSITAS ANDALAS, 2017)
Avocado is a cross-pollinated plant that has many variations of morphology. The study aimed to classify avocado accession based on morphological characters and to evaluate avocado accession based on predefined idiotype. The research has been conducted in January and February 2015 in three sub-districts in Solok District, representing lowland, middle and highland. The characters observed were morphological characters, both qualitative and quantitative in accordance with Descriptors for Avocado (IPGRI 1995). The calculation of genetic distance between accessions was done by Gower method. The selection of idiotypes has been done by collecting information on consumer preferences on the characteristics of avocado from fruit shops, fruit traders in traditional markets, farmers, and consumers. The results showed that 21 avocado accession of Solok regency can be grouped into two main groups, namely Idal 3 avocados and 20 other accessions. The coefficient of dissimilarity between the two groups is about 45% or with a similarity of 55%. Accessions that have many superior characters are the accession of Idal-1, Zainal and Asni-2.